Morals and Violence: Principles for a Historical and Social Cartography of Values (Global Journal of Human-Social Science, 2023)
In this article we seek to identify elements that make up part of a cartography of power a sequence of works related to a larger research Through the criminal processes of Mallet-PR in Brazil it was possible to find points that suggest a quite latent morality in society that configures an exercise of power crossing subjects institutions and knowledge When that moral was broken the response was almost immediate and violent From this we will see how the frontiers of legality right and wrong good and bad lose their dualistic character getting confused and reconstituted in other forms of relationships We identify here a violent process of maintenance of morals We deal with conceptualizations throughout the text with emphasis on violence relations in the first moment continuing with the questioning of morality in the second moment We hope that this conversation with history and philosophy will allow everyone a critical reading of their own social place
Keywords: historiography; cartography; criminal cases; moral; violence